Consumer Acceptability and Impact of Handling Conditions on Sensory, Microbiological and Nutritional Quality of Beet Leaves - Fernandez, María Verónica (2017)
Background and Objective: Beet leaves (BL) constitute a currently wasted but highly nutritious resource. The aims of this study were to assess Argentineans consumer habits towards beet leaves (BL) to determine how information affects consumers’ acceptability and to assess the impact of storage conditions on BL quality and shelf-life. Materials and Methods: A web-online survey was conducted and data of 416 respondents were analyzed. Then, quality evolution under different storage conditions (A: 25±1°C and 60-62% of relative humidity (RH), B: 5±1°C and 97-99% RH) were followed. Data were analyzed by two-way analysis of variance and Turkey-Kramer test (p<0.05). Results: Most consumers (79%) don’t use BL due to the poor state at retailers and/or the lack of knowledge about their nutritional value but when this information was provided, acceptability (p<0.05) increased significantly. BL quality was severely affected by storage conditions. "A" condition introduces a rapid drop in sensory quality, losses of 60-82% in bioactives complete loss of antioxidant activity (in 9 days) and severe injure of microbiological quality. Conversely, at "B" condition significantly lower losses in quality attributes were detected, reaching a shelf-life extension of at least 14 days. Conclusion: Development of a product based on BL requires the improvement of handling conditions as well as increasing efforts to inform consumers about their benefits. Through this recovery, economic, environmental and social profits could be achieved.